A severe case of cardiospondylocarpofacial syndrome with a novel MAP3K7 variant - Hiromi Nyuzuki; Junichi Ozawa; Keisuke Nagasaki; Yosuke Nishio; Tomoo Ogi; Jun Tohyama; Takeshi Ikeuchi (Human Genome Variation)
Abstract Cardiospondylocarpofacial syndrome (CSCFS) is a congenital malformation characterized by growth retardation, facial features, short toes with carpal and tarsal fusion, extensive posterior neck vertebral fusion, congenital heart disease, and deafness. Here, we report a severe case of CSCFS with a novel variant, p.Thr187Ile, in MAP3K7. Thr187 is the main phosphorylation site for TGF-beta-activated kinase 1 encoded by MAP3K7, and this variant may cause significant abnormalities in downstream signaling.